2011
DOI: 10.1084/jem.20110363
|View full text |Cite
|
Sign up to set email alerts
|

Initial antibodies binding to HIV-1 gp41 in acutely infected subjects are polyreactive and highly mutated

Abstract: Many HIV-1 envelope-reactive antibodies shortly after HIV-1 transmission may arise from crow-reactive memory B cells previously stimulated by non-HIV-1 host or microbial antigens

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
264
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 195 publications
(273 citation statements)
references
References 47 publications
8
264
0
1
Order By: Relevance
“…Second, the TF Env may not engage the HIV-1 antibody UCA but rather engages latter members of the antibody lineage (Figure 6). We have found this to be the case with commonly made non-broadly neutralizing gp41 Env antibodies that are the first to arise in HIV-1 infection, for which the gp41 lineage was initiated by antigens derived from the microbiome before HIV-1 infection and, upon HIV-1 infection, gp41 Env engaged cross-reactive affinity matured B cells (9092) (Figure 6). Diversion of pre-existing B cell responses to non-HIV antigens may be at play for some bnAb UCAs as well.…”
Section: B Cell Lineage Immunogen Designmentioning
confidence: 85%
See 1 more Smart Citation
“…Second, the TF Env may not engage the HIV-1 antibody UCA but rather engages latter members of the antibody lineage (Figure 6). We have found this to be the case with commonly made non-broadly neutralizing gp41 Env antibodies that are the first to arise in HIV-1 infection, for which the gp41 lineage was initiated by antigens derived from the microbiome before HIV-1 infection and, upon HIV-1 infection, gp41 Env engaged cross-reactive affinity matured B cells (9092) (Figure 6). Diversion of pre-existing B cell responses to non-HIV antigens may be at play for some bnAb UCAs as well.…”
Section: B Cell Lineage Immunogen Designmentioning
confidence: 85%
“…Among the microbiota-induced memory B cells, we have demonstrated that some cells can cross-react with HIV gp41 Env (9092). Transmitted/founder virus Env can engage these mutated cells, even if the unmutated ancestor naïve B could not, and diverge clonal evolution to affinity maturation against Env (green pathway).…”
Section: Figurementioning
confidence: 99%
“…These studies also found no differences in V H use, although, again, the number of sequences studied was small. In contrast, studies have found differences in D segment use between antibodies with short and long CDR3s, including the appearance of tandem D gene segments in very long CDR3s, suggesting a potential causative relationship (4,12). However, these studies did not investigate whether these differences were a sign of selection during B-cell maturation.…”
mentioning
confidence: 83%
“…The earliest changes to the virus population are driven by the CD8 + T‐cell response that is induced as viremia increases39 and places strong selection pressure on the virus, resulting in complete turnover of the virus pool within the first few weeks of infection 40. The development of antibody responses follows a pattern, with antiviral antibodies being detected first as immune complexes41 followed by free antibody directed at the HIV‐1 envelope (Env) glycoprotein 41 (gp41) subunit,41, 42 and then by the development of Env glycoprotein 120 (gp120)‐binding antibodies 41. These early antibody responses do not neutralize or place selective pressure on virus evolution41; antibodies capable of neutralizing autologous viruses are not detectable until weeks to months after infection is established19, 20 and have little to no activity against heterologous HIV‐1 strains 43.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%
“…It is possible that trafficking of the negative regulatory factor (Nef) protein from HIV‐1‐infected macrophages to B cells may alter class switching and germinal center (GC) responses,58 but dysfunction is also likely driven by the early cytokine storm59 and ongoing immune dysfunction caused by HIV‐1 infection of T cells. B‐cell dysregulation is evidenced by the delayed antibody response in acute HIV‐1 infection,41 an increase in the proportion of activated memory B cells and exhausted B cells, non‐specific plasmablast activation (leading to polyclonal immunoglobulin production), and a decline in the frequency of long‐lived plasma cells 42, 60, 61, 62, 63. In addition, Env‐specific B cells are found in the activated and exhausted B‐cell subsets in viremic individuals 64.…”
Section: Development Of Broadly Neutralizing Antibodies In Hiv‐1 Infementioning
confidence: 99%